2001
DOI: 10.1089/08977150151070937
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Encapsulated BDNF-Producing Fibroblasts into the Injured Spinal Cord Without Immune Suppression in Adult Rats

Abstract: Grafting of genetically modified cells that express therapeutic products is a promising strategy in spinal cord repair. We have previously grafted BDNF-producing fibroblasts (FB/BDNF) into injured spinal cord of adult rats, but survival of these cells requires a strict protocol of immune suppression with cyclosporin A (CsA). To develop a transplantation strategy without the detrimental effects of CsA, we studied the properties of FB/BDNF that were encapsulated in alginate-poly-L-ornithine, which possesses a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 52 publications
4
57
0
Order By: Relevance
“…Other positively charged surfaces, such as poly-L-lysine, but not PLO, have been used previously to facilitate the formation of hepatocyte aggregates exhibiting liver-specific functions [Tzanakakis et al, 2001]. PLO, similar to other polycations especially poly-L-lysine, has been used mostly in combination with other molecules for various applications such as non-viral gene delivery [Fimmel et al, 2000;Ramsay and Gumbleton, 2002;Brown et al, 2003], packaging system (in alginate beads) for cellular grafts [Tobias et al, 2001;Calafiore, 2003], or as attachment matrix/ scaffold for neuronal and embryonic stem cell cultures [Murashov et al, 2005;Flanagan et al, 2006;Morizane et al, 2006]. Polyamino acids, such as PLO, have also been shown to activate cell signaling pathways [Haber et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…Other positively charged surfaces, such as poly-L-lysine, but not PLO, have been used previously to facilitate the formation of hepatocyte aggregates exhibiting liver-specific functions [Tzanakakis et al, 2001]. PLO, similar to other polycations especially poly-L-lysine, has been used mostly in combination with other molecules for various applications such as non-viral gene delivery [Fimmel et al, 2000;Ramsay and Gumbleton, 2002;Brown et al, 2003], packaging system (in alginate beads) for cellular grafts [Tobias et al, 2001;Calafiore, 2003], or as attachment matrix/ scaffold for neuronal and embryonic stem cell cultures [Murashov et al, 2005;Flanagan et al, 2006;Morizane et al, 2006]. Polyamino acids, such as PLO, have also been shown to activate cell signaling pathways [Haber et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, adult SCI is similarly known to alter p75 expression (Ji et al, 2015;King et al, 2000;Liebl et al, 2001), which could potentially affect the action of exogenously applied BDNF. In contrast to these inconsistent effects on CST regeneration, many studies have reported regrowth of 5HT fibers in response to BDNF administration (Boyce et al, 2007;Brock et al, 2010;Coumans et al, 2001;Golden et al, 2007;Koda et al, 2007;Lu et al, 2005;Tobias et al, 2001), which has the potential to facilitate locomotor recovery (Slawinska, Miazga, & Jordan, 2014).…”
Section: Neuroprotection Sparing and Growth With Bdnfmentioning
confidence: 99%
“…After direct AAV injection, sustained expression of BDNF and NT-3 has been described in cells in the injured spinal cord up to 16 weeks' postinjection . In contrast, downregulation of the BDNF gene in encapsulated fibroblasts 2 weeks after transplantation into an adult rat cervical SCI was reported (Tobias et al, 2001). Interestingly, expression returned when the cells were harvested and put back into culture, "suggesting that soluble factors originating from the host immune response may contribute to the down-regulation" (Tobias et al, 2001).…”
Section: Mode Of Neurotrophic Factor Deliverymentioning
confidence: 99%
“…As the cross-linking multivalent cations gradually diffuse out from the gel, it slowly degrades and is excreted in urine. Alginate gels are frequently used as matrices for encapsulation of living cells and for the release of proteins (Novikova et al, 2006;Tobias et al, 2001Tobias et al, , 2005. In regeneration studies, alginate gels are often applied as cell carrier substances.…”
Section: Alginatementioning
confidence: 99%